Would personal carbon trading reduce travel emissions more effectively than a carbon tax?. (March 2015) - Raux, Charles; Croissant, Yves; Pons, Damien
Highlights: We compare the effectiveness of personal carbon trading with the carbon tax. We conduct a stated preferences survey ( N  ∼ 300). Personal carbon trading could effectively reduce emissions from personal travel. No significant difference in effectiveness could be proved with the carbon tax. Abstract: The application of personal carbon trading (PCT) to transport choices has recently been considered in the literature as a means of reducing CO2 emissions. Its potential effectiveness in changing car travel behavior is compared to the conventional carbon tax (CT) by means of a stated preferences survey conducted among French drivers ( N  ∼ 300). We show evidence that PCT could effectively change travel behavior and hence reduce transport emissions from personal travel. There is however a definite reluctance to reduce car travel. We were unable to demonstrate any significant difference between the effectiveness of PCT and the CT with regard to changing travel behavior. However, in the experiment, the PCT scheme provided consistent results while this was not the case for the CT scheme. Further research is needed into the "social norm" conveyed by a personal emissions allowance.